High-anti-reflection nano coating for perovskite solar cell TCO glass and preparation method of high-anti-reflection nano coating
By coating the perovskite solar cell TCO glass with high transparency nanocoating composed of composite silica, polyhydroxy polymer and wetting leveling agent on the perovskite solar cell TCO glass, the problems of low transmittance and poor mechanical properties are solved, and the effects of high transparency, good mechanical properties and long service life are achieved.
Patent Information
- Application Number
- CN202510069949.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The perovskite solar cell TCO glass has a low transmittance, and the existing nano-transparent coating technology has problems such as poor mechanical properties and short service life.
An organic-inorganic hybrid nanocoat is formed by a high-relief nanocoat consisting of a composite silica dispersion, a polyhydroxy polymer dispersion and a wetting leveling agent.
It has achieved high transmittance performance of perovskite solar cell TCO glass, improved light transmittance by 3.5 to 4.5%, and has good mechanical properties and self-cleaning function, and has a long service life.
Smart Images

Figure CN119875504A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a high-reflectivity nano coating for transparent conductive oxide (TCO) glass of perovskite solar cells and a preparation method thereof. Background Art
[0002] Solar cells are devices that use semiconductor materials to absorb sunlight and convert it into electrical energy. When sunlight shines on a solar cell, electrons in the semiconductor material are excited, generating an electric current. Depending on the semiconductor material used, solar cells can be divided into the following types: silicon-based solar cells, thin-film solar cells, and perovskite solar cells.
[0003] In order to protect the internal structure of solar cells, photovoltaic glass or TCO glass is usually used as a cover. However, when sunlight enters the surface of the cover glass, due to the difference in the refractive index of the medium, part of the light will be reflected, thereby reducing the absorption of the incident light by the solar cell. Therefore, an optical anti-reflection coating (anti-reflection film or anti-reflection film) is usually made on the light-facing surface of the solar cell to reduce reflected light, increase transmitted light, and achieve higher photoelectric conversion efficiency of the solar cell.
[0004] Traditional silicon-based solar cells increase the transmittance of photovoltaic glass by embossing it and applying an anti-reflection coating, and the transmittance of the treated photovoltaic glass can reach more than 94%. The transmittance of TCO glass used in perovskite solar cells is usually between 80% and 90%. Due to the special structure of perovskite solar cells, TCO glass cannot be embossed, so applying an anti-reflection coating is an effective way to solve the low transmittance of TCO glass in perovskite solar cells.
[0005] The preparation of photovoltaic glass anti-reflective coating usually requires annealing treatment above 600°C to achieve good anti-reflective and mechanical properties of the coating. However, TCO glass cannot be annealed above 600°C, so it needs to be coated using a room temperature coating process.
[0006] In the prior art, there are not many anti-reflective nano-coating technologies for perovskite solar cell TCO glass. Conventional anti-reflective coatings are mostly low-refractive index materials. Silicon dioxide is a common low-refractive index optical coating material. At the same time, silicon dioxide coatings can be prepared at room temperature. Therefore, silicon dioxide coatings can be used for anti-reflective coatings of TCO glass.
[0007] The room temperature preparation of silica coating mostly adopts the sol-gel method. The preparation methods of silica sol are mainly divided into two types: acid catalysis and base catalysis. The silica coating prepared by the acid catalysis method has higher mechanical properties, but the anti-reflection performance is not outstanding; the silica coating prepared by base catalysis has higher anti-reflection performance, but the mechanical properties are poor. For example, patent application No. 202411629896.X discloses a self-cleaning anti-reflection coating liquid and its preparation method and application. The film material obtained after the coating of the coating liquid has the advantages of high anti-reflection and high weather resistance, but the mechanical properties are poor. The above problems can be solved by the acid-base two-step catalytic method, that is, by compounding the acid-catalyzed sol with the base-catalyzed sol or first preparing the acid-catalyzed (base-catalyzed) sol and then performing the base catalysis (acid catalysis) treatment to obtain the acid-base two-step catalytic sol, and then an optical coating with high anti-reflection and good mechanical properties can be prepared. However, the silica sol prepared by the acid-base two-step catalytic method has the disadvantages of poor sol stability and short life, which limits its large-scale application.
[0008] For example, patent application number CN201010587173.X proposes a large-area silicon-based thin-film solar cell with an anti-reflection film and a preparation method thereof, which is prepared by an acid-base two-step catalytic method. A layer of anti-reflection film is prepared on photovoltaic glass by a sol-gel method, and combined with the front electrode TCO film of the battery to obtain a double-layer anti-reflection effect. The sol preparation scheme of the anti-reflection film is an acid-base two-step catalytic method, that is, hydrochloric acid and ammonia water are used successively for acid catalysis and base catalysis to synthesize silicon dioxide. Although this method can obtain a SiO2 film with a continuously adjustable refractive index in the range of 1.1 to 1.4, which can have a good anti-reflection effect on TCO glass, the stability of the sol cannot be maintained for a long time, and under the subsequent long-term action of base catalysis, the mechanical properties of the prepared anti-reflection film will become worse and worse.
[0009] Based on the above technical background, providing a preparation method for a silicon dioxide coating having high antireflection, good mechanical properties and long service life is crucial to improving the performance of TCO glass for perovskite solar cells. Summary of the invention
[0010] Based on the above technical background, the main purpose of the present invention is to provide a high anti-reflection nano-coating for TCO glass of perovskite solar cells and a preparation method thereof, which solves the problem of low transmittance of TCO glass of existing perovskite solar cells.
[0011] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0012] The first aspect of the present invention is to provide a high anti-reflection nano coating for perovskite solar cell TCO glass, wherein the high anti-reflection nano coating for perovskite solar cell TCO glass is prepared from the following raw materials in parts by weight:
[0013] 2 to 10 parts by weight of composite silicon dioxide dispersion;
[0014] 90-98 parts by weight of polyhydroxy polymer dispersion;
[0015] Wetting and leveling agent 0.01 to 1 part by weight.
[0016] Preferably, the composite silicon dioxide dispersion is prepared from the following raw materials in parts by weight:
[0017]
[0018] Preferably, the polyhydroxy polymer dispersion is prepared by dispersing a polyhydroxy polymer in a mixed solvent, and the mass fraction of the polyhydroxy polymer dispersion is 1-5%.
[0019] Preferably, the wetting and leveling agent is selected from one or both of gemini siloxane and acetylene glycol vinyl ether.
[0020] The second aspect of the present invention is to provide a method for preparing the high anti-reflection nano coating for TCO glass of perovskite solar cells according to the first aspect of the present invention, the preparation method comprising the following steps:
[0021] Step 1, mixing a composite silicon dioxide dispersion, a polyhydroxy polymer dispersion and a wetting and leveling agent, and stirring them evenly to obtain a high anti-reflection nano coating liquid;
[0022] Step 2: Apply the high anti-reflection nano coating liquid and solidify it at room temperature to obtain the high anti-reflection nano coating of the perovskite solar cell TCO glass.
[0023] In step 1,
[0024] Preferably, the composite silicon dioxide dispersion is slowly added to the polyhydroxy polymer dispersion, and then the wetting and leveling agent is added, and the mixture is stirred at a rotation speed of 50 to 500 rpm for 5 to 20 minutes.
[0025] Preferably, the method for preparing the composite silicon dioxide dispersion comprises the following steps:
[0026] Step a, dividing the organic solvent into two parts, mixing one part of the organic solvent with water and ammonia water to obtain liquid A, and mixing the other part of the organic solvent with alkoxysilane to obtain liquid B;
[0027] Step b, slowly adding liquid B into liquid A, stirring the mixture for reaction and then standing it for aging to obtain a silica sol;
[0028] Step c: Compounding silica sols of different particle sizes by graded mixing, heating under vacuum conditions, then adding water, heating and concentrating, to obtain a composite silica dispersion.
[0029] In step a,
[0030] Preferably, the organic solvent is selected from one or more of methanol, ethanol, ethylene glycol, n-propanol, and isopropanol;
[0031] Preferably, the concentration of the aqueous ammonia is 25-28wt%;
[0032] Preferably, the alkoxysilane is selected from one or more of tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, tetramethoxysilane, dimethyldimethoxysilane and dimethyldiethoxysilane.
[0033] In step b,
[0034] Preferably, at room temperature, liquid B is slowly added to liquid A, and the mixture is stirred at a rotation speed of 50 to 500 rpm for 2 to 5 hours. After the reaction is completed, the mixture is allowed to stand for 2 to 10 days to obtain a silica sol.
[0035] In step c,
[0036] Preferably, silica sols of different particle sizes are graded and composited, heated to boiling under vacuum conditions below 5 kPa, some organic solvents and ammonia water are removed, water is added, and the sol is further heated to boiling under vacuum conditions below 5 kPa to concentrate the mass fraction of the silica sol to 20-30 wt %, thereby obtaining a composite silica dispersion;
[0037] The silica sols with different particle sizes are selected from two or more of the silica sols with super large particle size of 100-200nm, large particle size of 60-100nm, medium particle size of 30-60nm, small particle size of 10-30nm and super small particle size of 1-10nm.
[0038] The beneficial effects of the present invention are:
[0039] (1) The high anti-reflection nano coating for perovskite solar cell TCO glass is prepared from a composite silica dispersion, a polyhydroxy polymer dispersion and a wetting and leveling agent. The present invention uses a polyhydroxy polymer as a binder to make the high anti-reflection nano coating liquid have higher stability and lifespan, and has higher mechanical properties than the silica coating prepared by acid-base compounding;
[0040] The present invention adopts composite nano-silicon dioxide with a certain gradation as the anti-reflection material, which can improve the mechanical properties of the high anti-reflection nano-coating and make the coating super-hydrophilic. After coating, the self-cleaning property of the perovskite solar cell panel can be achieved.
[0041] (2) The high-reflectivity nano-coating of the present invention can increase the light transmittance of the TCO glass of the perovskite solar cell by 3.5-4.5%.
[0042] (3) The method for preparing the high anti-reflection nano coating of the present invention is to introduce a polyhydroxy polymer as a binder into nano-silicon dioxide, and to form an organic-inorganic hybrid nano coating by a condensation reaction between composite nano-silicon dioxide particles of a certain grade and the polyhydroxy polymer. Compared with conventional anti-reflection coatings, the anti-reflection nano coating of the present invention can be prepared at room temperature and is suitable for perovskite solar cells. It can increase the light transmittance of TCO glass of perovskite solar cells and also has excellent mechanical properties and self-cleaning functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The transmittance images of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and FTO glass are shown;
[0044] Figure 2 The transmittance images of Example 3 and ITO glass are shown;
[0045] Figure 3 A cross-sectional view of the high anti-reflective nano-coating and the perovskite solar cell prepared in Example 1 and a SEM image of the high anti-reflective nano-coating are shown. DETAILED DESCRIPTION
[0046] The present invention will be described in detail below, and the characteristics and advantages of the present invention will become clearer and more distinct with the description.
[0047] The first aspect of the present invention is to provide a high anti-reflection nano coating for perovskite solar cell TCO glass, wherein the high anti-reflection nano coating for perovskite solar cell TCO glass is prepared from the following raw materials in parts by weight:
[0048] 2 to 10 parts by weight of composite silicon dioxide dispersion;
[0049] 90-98 parts by weight of polyhydroxy polymer dispersion;
[0050] Wetting and leveling agent 0.01 to 1 part by weight.
[0051] Preferably, the high anti-reflection nano coating for perovskite solar cell TCO glass is made from the following raw materials in parts by weight:
[0052] 5-6 parts by weight of composite silicon dioxide dispersion;
[0053] 93.98 to 94.95 parts by weight of polyhydroxy polymer dispersion;
[0054] Wetting and leveling agent 0.02-0.1 parts by weight.
[0055] The composite silicon dioxide dispersion is prepared from the following raw materials in parts by weight:
[0056]
[0057] Preferably, the composite silicon dioxide dispersion is prepared from the following raw materials in parts by weight:
[0058]
[0059] The polyhydroxy polymer dispersion is prepared by dispersing the polyhydroxy polymer in a mixed solvent, and the mass fraction of the polyhydroxy polymer dispersion is 1-5%.
[0060] Preferably, the mass fraction of the polyhydroxy polymer dispersion is 1.8-2.5%.
[0061] The wetting and leveling agent is selected from one or two of gemini siloxane and acetylene glycol vinyl ether.
[0062] Preferably, the wetting and leveling agent is gemini siloxane, acetylene glycol vinyl ether or a mixture of gemini siloxane and acetylene glycol vinyl ether.
[0063] When the wetting and leveling agent is a mixture of gemini siloxane and acetylene glycol vinyl ether, the mass ratio of gemini siloxane to acetylene glycol vinyl ether is 2:1.
[0064] The second aspect of the present invention is to provide a method for preparing the high anti-reflection nano coating for TCO glass of perovskite solar cells according to the first aspect of the present invention, the preparation method comprising the following steps:
[0065] Step 1, mixing a composite silicon dioxide dispersion, a polyhydroxy polymer dispersion and a wetting and leveling agent, and stirring them evenly to obtain a high anti-reflection nano coating liquid;
[0066] Step 2: Apply the high anti-reflection nano coating liquid on the medium and solidify it at room temperature to obtain the high anti-reflection nano coating of the perovskite solar cell TCO glass.
[0067] The above steps are described in detail below.
[0068] In step 1, the composite silica dispersion is slowly added to the polymer dispersion, and then a wetting and leveling agent is added, and the mixture is stirred at a speed of 50 to 500 rpm for 5 to 20 minutes.
[0069] Preferably, stirring is carried out at 250 rpm for 10 min.
[0070] According to a preferred embodiment of the present invention, the method for preparing the composite silicon dioxide dispersion comprises the following steps:
[0071] Step a, dividing the organic solvent into two parts, mixing one part of the organic solvent with water and ammonia water to obtain liquid A, and mixing the other part of the organic solvent with alkoxysilane to obtain liquid B;
[0072] Step b, slowly adding liquid B into liquid A, stirring the mixture for reaction and then standing it for aging to obtain a silica sol;
[0073] Step c: Compounding silica sols of different particle sizes by graded mixing, heating under vacuum conditions, then adding water, heating and concentrating, to obtain a composite silica dispersion.
[0074] Preferably, in step a, the organic solvent is selected from one or more of methanol, ethanol, ethylene glycol, n-propanol and isopropanol.
[0075] Preferably, the organic solvent is ethanol, methanol or isopropanol.
[0076] The concentration of the ammonia water is 25-28 wt %.
[0077] The alkoxysilane is selected from one or more of tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, tetramethoxysilane, dimethyldimethoxysilane and dimethyldiethoxysilane.
[0078] Preferably, the alkoxysilane is tetraethoxysilane, tetramethoxysilane or a mixture of tetraethoxysilane and methyltriethoxysilane.
[0079] In step b, liquid B is slowly added to liquid A at room temperature, and the mixture is stirred at a speed of 50 to 500 rpm for 2 to 5 hours. After the reaction is completed, the mixture is allowed to stand for 2 to 10 days to obtain a silica sol.
[0080] Preferably, at room temperature, solution B is slowly added to solution A, and the mixture is stirred at a rotation speed of 300 rpm for 2 to 3 hours. After the reaction is completed, the mixture is allowed to stand and age for 5 days to obtain a silica sol.
[0081] In step c, by controlling the amount of ammonia or water added, nano-silica sols with different particle sizes can be obtained, including ultra-large particle size (100-200nm), large particle size (60-100nm), medium particle size (30-60nm), small particle size (10-30nm), and ultra-small particle size (1-10nm).
[0082] Silica sols of different particle sizes are graded and composited, heated to boiling under vacuum conditions below 5 kPa, and after removing part of the organic solvent and the alkali catalyst, a certain amount of water is added, and the sol is continued to be heated to boiling under vacuum conditions below 5 kPa to concentrate the mass fraction of the silica sol to 20-30wt%, thereby obtaining a composite silica dispersion with a certain grade.
[0083] The silica sols with different particle sizes are selected from two or more of the silica sols with super large particle size, large particle size, medium particle size, small particle size and super small particle size.
[0084] The grading relationship of the super large particle size, large particle size, medium particle size, small particle size and super small particle size silica sol is (0-2):(0-3):(0-4):(1-5):1, calculated based on silica solid content.
[0085] Silica gel of different particle sizes is graded and compounded. After compounding, small particles can adhere to large particles. On the one hand, it can increase the surface roughness of the coating and achieve a super hydrophilic effect. On the other hand, relatively small particles can fill the gaps between large particles and can also serve as a "bridge" to connect large particles, so that there are more connection sites between large particles, thereby achieving better mechanical properties of the coating.
[0086] According to a preferred embodiment of the present invention, the method for preparing the polyhydroxy polymer dispersion comprises the following steps:
[0087] The polyhydroxy polymer is added into the mixed solvent and dispersed evenly to obtain a polyhydroxy polymer dispersion with a mass fraction of 1 to 5%.
[0088] Preferably, the mass fraction of the polyhydroxy polymer dispersion is 1.8-2.5%.
[0089] The polyhydroxy polymer is selected from one or more of polyvinyl alcohol (PVA), polyacrylic acid (PAA), polysiloxane, polysilazane and epoxy resin.
[0090] Preferably, the polyhydroxy polymer is selected from one or more of polysiloxane, polysilazane, polyvinyl alcohol and polyacrylic acid.
[0091] More preferably, the polyhydroxy polymer is obtained by mixing polysiloxane and polysilazane in a mass ratio of 10:1.
[0092] Alternatively, the polyhydroxy polymer is obtained by mixing polysiloxane and polyvinyl alcohol in a mass ratio of 5:1.
[0093] Alternatively, the polyhydroxy polymer is obtained by mixing polysiloxane and polyacrylic acid in a mass ratio of 20:1.
[0094] The polyhydroxy polymer described in the present invention is mainly a water-soluble polymer, which is characterized by having a certain chain length, containing abundant hydroxyl groups or generating abundant hydroxyl groups after hydrolysis, and being miscible with water or other hydrophilic polar solvents.
[0095] The mixed solvent is selected from one or more of water, methanol, ethanol, ethylene glycol, n-propanol and isopropanol.
[0096] Preferably, the mixed solvent is selected from one or more of water, ethanol and isopropanol.
[0097] More preferably, the mixed solvent is water and ethanol mixed in a volume ratio of (1-2):(1-4).
[0098] Alternatively, the mixed solvent is obtained by mixing water:ethanol:isopropanol in a volume ratio of 1:2:2.
[0099] In step 2, the medium is a TCO glass panel. Preferably, the high anti-reflection nano coating liquid is coated on the TCO glass panel.
[0100] The coating method is preferably spray coating, roller coating or spin coating.
[0101] When spraying or roller coating is adopted, the high anti-reflection nano coating liquid is coated on the TCO glass panel at a coating speed of 3 to 8 m / min and cured at room temperature for 5 to 20 minutes.
[0102] Preferably, the high anti-reflection nano coating liquid is coated on the TCO glass panel at a coating speed of 6 m / min and cured at room temperature for 10 minutes.
[0103] When spin coating is adopted, the spin coating is carried out at a spin coating speed of 1000 to 2000 rpm and an acceleration of 100 to 300 rpm. The spin coating time is 20 to 45 s. After the spin coating is completed, the material is cured at room temperature for 5 to 20 min.
[0104] Preferably, the spin coating is performed at a spin coating speed of 1500 rpm and an acceleration of 200 rpm for 30 s. After the spin coating is completed, the coating is cured at room temperature for 10 min.
[0105] Example
[0106] The present invention is further described below by specific examples, which are limited to illustrating the present invention but not to limiting the scope of the present invention. The raw materials used in the examples of the present invention were all purchased.
[0107] Example 1
[0108] Step 1, preparation of composite silicon dioxide dispersion:
[0109] Weigh 11.5 parts by weight of tetraethoxysilane, 85 parts by weight of ethanol as an organic solvent, 0.2 to 2 parts by weight of aqueous ammonia (the concentration of aqueous ammonia is 25-28 wt%), and 3.5 parts by weight of water.
[0110] The ethanol was divided into two parts, one part of the ethanol was mixed with water and ammonia water to obtain liquid A; the other part of the ethanol was mixed with tetraethoxysilane to obtain liquid B.
[0111] At room temperature, liquid B was slowly added to liquid A and stirred at a speed of 300 rpm. After reacting for 3 hours, the solution was allowed to stand for 5 days to obtain a nano-silica sol.
[0112] By controlling the amount of ammonia added, nano-silica sols with different particle sizes can be obtained, including large particle size (60-100nm), medium particle size (30-60nm), small particle size (10-30nm), and ultra-small particle size (1-10nm).
[0113] The silica sols of different particle sizes are graded and composited according to different quantitative relationships. The grading relationship of the medium, small and ultra-small particle sizes of the nano silica sol is 0.1:1:1 (ratio of silica solid content). After heating to a boiling state under a vacuum condition of less than 5 kPa to remove part of the organic solvent and the alkaline catalyst, a certain amount of water is added, and the sol is continued to be heated to boiling under a vacuum condition of less than 5 kPa to concentrate the mass fraction of the silica sol to 20wt%, and a composite silica aqueous dispersion with a certain grade is obtained.
[0114] Silica silica particles of different particle sizes are graded. After compounding, small particles can adhere to large particles. On the one hand, it can increase the surface roughness of the coating and achieve a super hydrophilic effect. On the other hand, relatively small particles can fill the gaps between large particles and can also serve as a "bridge" to connect large particles, so that there are more connection sites between large particles, thereby achieving better mechanical properties of the coating.
[0115] Step 2, preparation of polyhydroxy polymer dispersion:
[0116] The polyhydroxy polymer described in the present invention is mainly a water-soluble polymer, which is characterized by having a certain chain length, containing abundant hydroxyl groups or generating abundant hydroxyl groups after hydrolysis, and being miscible in water or other hydrophilic polar solvents.
[0117] The polysiloxane and polysilazane are mixed in a mass ratio of 10:1 to obtain a polyhydroxy polymer mixture. The polyhydroxy polymer mixture is uniformly dispersed in a mixed solvent to obtain a polyhydroxy polymer dispersion with a mass fraction of 1.8%. The mixed solvent is a mixed solution of water and ethanol, and the volume ratio of water:ethanol is 2:1.
[0118] Step 3, preparation of high anti-reflection nano coating liquid:
[0119] Weigh 6 parts by weight of a composite silica aqueous dispersion having a certain gradation relationship, 93.98 parts by weight of a polyhydroxy polymer dispersion, and 0.02 parts by weight of a wetting and leveling agent, gemini siloxane.
[0120] The composite silicon dioxide dispersion in step 1 is slowly added to the polyhydroxy polymer dispersion in step 2, and then the wetting and leveling agent Gemini siloxane is added, and the mixture is stirred at a speed of 50-500 rpm for 10 minutes to obtain a high-transmittance nano coating liquid.
[0121] Step 4, preparation of high anti-reflection nano-coating of TCO glass for perovskite solar cells:
[0122] In this embodiment, a roller coating process is adopted to load the high anti-reflection nano coating liquid into the coating equipment, and the coating is applied on the TCO glass panel of the perovskite solar cell at a transmission speed of 6 m / min. After curing at room temperature for 10 minutes, the high anti-reflection nano coating of the TCO glass of the perovskite solar cell can be obtained, and the film thickness is measured to be 115 nm.
[0123] The TCO glass used is fluorine-doped tin oxide conductive glass (FTO glass), with a size of 30 cm*30 cm and a thickness of 3.2 mm.
[0124] Example 2
[0125] Step 1, preparation of composite silicon dioxide dispersion:
[0126] Weigh 9.5 parts by weight of tetramethoxysilane, 85 parts by weight of organic solvent methanol, 0.1-1.5 parts by weight of aqueous ammonia (with an ammonia concentration of 25-28 wt%), and 5 parts by weight of water.
[0127] Methanol was divided into two parts, one part of the methanol was mixed evenly with water and ammonia water to obtain liquid A; the other part of the methanol was mixed evenly with tetramethoxysilane to obtain liquid B.
[0128] At room temperature, liquid B was slowly added to liquid A and stirred at a speed of 300 rpm. After reacting for 2 hours, the mixture was allowed to stand for 5 days to obtain a nano-silica sol.
[0129] By controlling the amount of ammonia added, nano-silica sols with different particle sizes can be obtained, including small particle size (10-30nm) and ultra-small particle size (1-10nm).
[0130] The silica sols of different particle sizes are graded and composited according to different quantitative relationships. The grading relationship of the small and ultra-small particle size nano silica sols is 1.5:1 (ratio of silica solid content). After heating to a boiling state under a vacuum condition lower than 5 kPa to remove part of the organic solvent methanol and the alkali catalyst, a certain amount of water is added, and the sol is continued to be heated to boiling under a vacuum condition lower than 5 kPa to concentrate the mass fraction of the silica sol to 20wt%, and a composite silica aqueous dispersion with a certain gradation is obtained.
[0131] Step 2, preparation of polyhydroxy polymer dispersion:
[0132] The polysiloxane and polyvinyl alcohol are mixed in a mass ratio of 5:1 to obtain a polyhydroxy polymer mixture. The polyhydroxy polymer is evenly dispersed in a mixed solvent to obtain a polyhydroxy polymer dispersion with a mass fraction of 2%. The mixed solvent is a mixed solution of water and ethanol, and the volume ratio of water:ethanol is 1:4.
[0133] Step 3, preparation of high anti-reflection nano coating liquid:
[0134] Weigh 5 parts by weight of composite silica dispersion, 94.9 parts by weight of polyhydroxy polymer dispersion, and 0.1 parts by weight of wetting and leveling agent, wherein the wetting and leveling agent is a mixture of gemini siloxane and acetylene glycol vinyl ether, and the mass ratio thereof is 2:1.
[0135] The composite silicon dioxide aqueous dispersion with a certain gradation relationship in step 1 is slowly added to the polyhydroxy polymer dispersion in step 2, and then a wetting and leveling agent is added. After stirring at a speed of 50-500 rpm for 10 minutes, a high anti-reflection nano coating liquid is obtained.
[0136] Step 4, preparation of high anti-reflection nano-coating of TCO glass for perovskite solar cells:
[0137] In this embodiment, a roller coating process is adopted to load the high anti-reflection nano coating liquid into the coating equipment, and the coating is applied on the TCO glass panel of the perovskite solar cell at a transmission speed of 6 m / min. After curing at room temperature for 10 minutes, the high anti-reflection nano coating of the TCO glass of the perovskite solar cell can be obtained, and the film thickness is measured to be 129 nm.
[0138] The TCO glass used is fluorine-doped tin oxide conductive glass (FTO glass), with a size of 30 cm*30 cm and a thickness of 3.2 mm.
[0139] Example 3
[0140] Step 1, preparation of composite silicon dioxide dispersion:
[0141] Weigh 12 parts by weight of alkoxysilane, 82.7-87.2 parts by weight of organic solvent isopropanol, 0.3 parts by weight of ammonia water (ammonia water concentration is 25-28wt%), and 0.5-5 parts by weight of water. The alkoxysilane is tetraethoxysilane and methyltriethoxysilane, and the mass ratio of tetraethoxysilane to methyltriethoxysilane is 4:1.
[0142] Isopropyl alcohol was divided into two parts, one part of the isopropyl alcohol was mixed evenly with water and ammonia water to obtain liquid A; the other part of the isopropyl alcohol was mixed evenly with alkoxysilane to obtain liquid B.
[0143] At room temperature, liquid B was slowly added to liquid A and stirred at a speed of 300 rpm. After reacting for 2 hours, the mixture was allowed to stand for 5 days to obtain a nano-silica sol.
[0144] By controlling the amount of water added, nano-silica sols with different particle sizes can be obtained, including medium particle size (30-60nm), small particle size (10-30nm), and ultra-small particle size (1-10nm).
[0145] The silica sols of different particle sizes are graded and composited according to different quantitative relationships. The grading relationship of the medium particle size, small particle size and ultra-small particle size nano silica sol is 0.5:0.8:1 (ratio of silica solid content). After heating to a boiling state under a vacuum condition of less than 5 kPa to remove part of the organic solvent and the alkaline catalyst, a certain amount of water is added, and the sol is continued to be heated to boiling under a vacuum condition of less than 5 kPa to concentrate the mass fraction of the silica sol to 20wt%, and a composite silica aqueous dispersion with a certain grade is obtained.
[0146] Step 2, preparation of polyhydroxy polymer dispersion:
[0147] The polysiloxane and polyacrylic acid are mixed in a mass ratio of 20:1 to obtain a polyhydroxy polymer mixture. The polyhydroxy polymer mixture is uniformly dispersed in a mixed solvent to obtain a polyhydroxy polymer dispersion with a mass fraction of 2.5%. The mixed solvent is a mixed solution of water, ethanol and isopropanol, and the volume ratio is water: ethanol: isopropanol = 1:2:2.
[0148] Step 3, preparation of high anti-reflection nano coating liquid:
[0149] Weigh 5 parts by weight of a composite silica aqueous dispersion having a certain gradation relationship, 94.95 parts by weight of a polyhydroxy polymer dispersion, and 0.05 parts by weight of a wetting and leveling agent, gemini siloxane.
[0150] The composite silicon dioxide dispersion in step 1 is slowly added to the polyhydroxy polymer dispersion in step 2, and then a wetting and leveling agent is added. After stirring at a rotation speed of 50-500 rpm for 10 minutes, a high anti-reflection nano coating liquid is obtained.
[0151] Step 4, preparation of high anti-reflection nano-coating of TCO glass for perovskite solar cells:
[0152] In this embodiment, a spin coating process is adopted, and the TCO glass is placed in the center of the stage of the spin coater. The high anti-reflection nano coating liquid is added to the TCO glass, and the spin coating is performed at a rotation speed of 1500 rpm and an acceleration of 200 rpm. The spin coating time is 30 seconds. After completion, it is cured at room temperature for 10 minutes to obtain the high anti-reflection nano coating of the perovskite solar cell TCO glass. The film thickness is measured to be 125nm.
[0153] The TCO glass used is indium-doped tin oxide conductive glass (ITO glass), with a size of 5 cm*5 cm and a thickness of 1.1 mm.
[0154] Comparative Example
[0155] Comparative Example 1
[0156] The high anti-reflection nano-coating was prepared in a manner similar to Example 1, except that in step 1, a composite silica dispersion with a certain grade was not used, and only silica with a small particle size was used to prepare the aqueous dispersion.
[0157] Comparative Example 2
[0158] The high anti-reflection nano coating was prepared in a similar manner to Example 1, except that the polyhydroxy polymer in step 2 was polysiloxane.
[0159] Experimental example
[0160] Experimental Example 1 Performance Test
[0161] The transmittance, hardness, adhesion, water contact angle and transmittance attenuation tests were performed on the TCO glasses prepared in Examples 1-3 and Comparative Examples 1-2, respectively. The test results are shown in Table 1. The transmittance test was performed by spectrophotometry, and the test wavelength range was 380-780nm. FTO glass was used in Example 1, Example 2, Comparative Example 1 and Comparative Example 2. The transmittance of FTO glass was 81.1%. The transmittance image is shown in Table 1. Figure 1 Example 3 uses ITO glass, the transmittance of ITO glass is 83.8%, the transmittance image is shown Figure 2. The pencil hardness test method is tested in accordance with GB / T6739-2006 standard. The adhesion test method is carried out in accordance with IS09211-4:201 standard, and a cross-cutting test is performed on the sample coating surface with a cross-cutting tool. The cut edge should be completely smooth, without shedding, and is level 0. The test surface for the water contact angle is the coating surface, and the static water contact angle is tested for 5s. The test for transmittance attenuation is to conduct a pressure accelerated aging test at 121℃ and 100%RH for 24h. The transmittance changes before and after the test, that is, the transmittance attenuation △T = (transmittance before test - transmittance after test) / transmittance before test.
[0162] Table 1 Performance test results
[0163] Test items Light transmittance Pencil hardness Adhesion Water contact angle Transmittance attenuation △T Example 1 85.4% 2H Level 0 3.8° △T=0.47% Example 2 85.2% 3H Level 0 2.9° △T=0.21% Example 3 86.5% 3H Level 0 4.2° △T=0.55% Comparative Example 1 85.1% 2H Level 0 11.2° △T=1.24% Comparative Example 2 83.5% 2H Level 0 15.5° △T=0.86%
[0164] It can be seen from Table 1 that the transmittance of Examples 1 to 3 is 85.2% or more, which is higher than the transmittance of Comparative Examples 1 to 2; the pencil hardness of Examples 1 to 3 is 2H or more, which is higher than the hardness of Comparative Examples 1 to 2; the adhesion of Examples 1 to 2 is level 0, and the adhesion is high; the water contact angle of Examples 1 to 3 is below 4.2°, and the hydrophilicity of Examples 1 to 3 is higher than that of Comparative Examples 1 to 2; the transmittance attenuation of Examples 1 to 3 is lower than that of Comparative Examples 1 to 2.
[0165] from Figure 1 and Figure 2 It can be seen that the transmittance of Examples 1 and 2 is higher than that of FTO glass, and the transmittance of Example 3 is higher than that of ITO glass, indicating that coating the high-reflection-enhancing nano-coating of the present invention on the surface of FTO glass and ITO glass can improve the transmittance of TCO glass.
[0166] Experimental Example 2 SEM Test
[0167] The high anti-reflection nano-coating prepared in Example 1 was tested by scanning electron microscope. The test results are as follows: Figure 3 shown.
[0168] from Figure 3 It can be seen that in the high anti-reflection nano-coating, silica colloids of different particle sizes are evenly distributed, so that there are more connection sites between large silica particles, which is beneficial to the improvement of the mechanical properties of the high anti-reflection nano-coating.
[0169] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A high anti-reflection nano coating for perovskite solar cell TCO glass, characterized in that: The high anti-reflection nano coating for perovskite solar cell TCO glass is prepared from the following raw materials in parts by weight: 2 to 10 parts by weight of composite silicon dioxide dispersion; 90-98 parts by weight of polyhydroxy polymer dispersion; Wetting and leveling agent 0.01 to 1 part by weight.
2. The high anti-reflection nano coating for perovskite solar cell TCO glass according to claim 1, characterized in that: The composite silicon dioxide dispersion is prepared from the following raw materials in parts by weight:
3. The high anti-reflection nano coating for perovskite solar cell TCO glass according to claim 1, characterized in that: The polyhydroxy polymer dispersion is prepared by dispersing the polyhydroxy polymer in a mixed solvent, and the mass fraction of the polyhydroxy polymer dispersion is 1-5%.
4. The high anti-reflection nano coating for perovskite solar cell TCO glass according to claim 1, characterized in that: The wetting and leveling agent is selected from one or two of gemini siloxane and acetylene glycol vinyl ether.
5. A method for preparing a high anti-reflection nano coating for perovskite solar cell TCO glass according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Step 1, mixing a composite silicon dioxide dispersion, a polyhydroxy polymer dispersion and a wetting and leveling agent, and stirring them evenly to obtain a high anti-reflection nano coating liquid; Step 2: Apply the high anti-reflection nano coating liquid and solidify it at room temperature to obtain a high anti-reflection nano coating for the TCO glass of the perovskite solar cell.
6. The preparation method according to claim 5, characterized in that: In step 1, The composite silicon dioxide dispersion is slowly added into the polyhydroxy polymer dispersion, and then the wetting and leveling agent is added, and stirred at a speed of 50 to 500 rpm for 5 to 20 minutes.
7. The preparation method according to claim 5, characterized in that: In step 1, the preparation method of the composite silicon dioxide dispersion comprises the following steps: Step a, dividing the organic solvent into two parts, mixing one part of the organic solvent with water and ammonia water to obtain liquid A, and mixing the other part of the organic solvent with alkoxysilane to obtain liquid B; Step b, slowly adding liquid B into liquid A, stirring the mixture for reaction and then standing it for aging to obtain a silica sol; Step c: Compounding silica sols of different particle sizes by graded mixing, heating under vacuum conditions, then adding water, heating and concentrating, to obtain a composite silica dispersion.
8. The preparation method according to claim 7, characterized in that: In step a, The organic solvent is selected from one or more of methanol, ethanol, ethylene glycol, n-propanol, and isopropanol; The concentration of the aqueous ammonia is 25-28wt%; The alkoxysilane is selected from one or more of tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, tetramethoxysilane, dimethyldimethoxysilane and dimethyldiethoxysilane.
9. The preparation method according to claim 7, characterized in that: In step b, At room temperature, liquid B is slowly added to liquid A, and the mixture is stirred at a speed of 50 to 500 rpm for reaction for 2 to 5 hours. After the reaction is completed, the mixture is allowed to stand for 2 to 10 days to obtain a silica sol.
10. The preparation method according to claim 7, characterized in that: In step c, The silica sols with different particle sizes are graded and composited, heated to boiling state under vacuum conditions below 5 kPa, some organic solvents and ammonia water are removed, water is added, and the sol is further heated to boiling under vacuum conditions below 5 kPa to concentrate the mass fraction of the silica sol to 20-30 wt%, thereby obtaining a composite silica dispersion; The silica sols with different particle sizes are selected from two or more of the silica sols with super large particle size of 100-200nm, large particle size of 60-100nm, medium particle size of 30-60nm, small particle size of 10-30nm and super small particle size of 1-10nm.
Citation Information
Patent Citations
Large-area silicon-based thin film solar battery with anti-reflecting film and manufacturing method thereof
CN102104085A
Self-cleaning anti-reflection coating liquid as well as preparation method and application thereof
CN119144201A
Preparation method of high-light-transmittance, low-haze and super-hydrophobic SiO2 film
CN117567039A
Ultra-hydrophilic antireflective coating composition comprising siloxane compound, ultra-hydrophilic antireflective film using same, and method for preparing ultra-hydrophilic antireflective film
US20150291803A1
Silica-siloxane nanohybrid coating material and production method therefor
WO2018043987A1